Findings of orchids in Pivdenny Bug′s lowlands (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
New distributional, ecological and coenotic data concerning two orchids of Pivdenny Bug region are reported.
Keywords: Orchidaceae, Ukraine, Pivdenny Bug.